2022
DOI: 10.33096/woh.vi.253
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Jus Jambu Biji Merah (Psidium Guajava) Terhadap Meningkatkan Kadar Hemoglobin Pada Remaja Putri

Abstract: Anemia berkaitan dengan masalah kesehatan reproduksi terutama pada perempuan.Anemia yaitu kekurangan kadar hemoglobin (Hb) dalam darah yaitu kadar Hb <12 gr/dl .Remaja yang mengalami anemia akan mengakibatkan pertumbuhan dan perkembangan terganggu, lemah karena sering terkena infeksi, Tujuan penelitian ini untuk mengetahui pengaruh pemberian jus jambu biji merah terhadap kadar hemoglobin pada remaja putri.Penelitian ini menggunakan Quasi Eksperimental desain one group pretest postest design.Rancangan peneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…In addition, according to Rusdi's research (2018) which shows that there is an effect of giving red guava juice on hemoglobin levels of anemic adolescent girls with p value = <0.001. This is in line with Handayani's (2021) study which showed that guava juice had an effect on increasing hemoglobin levels in adolescent girls.…”
Section: Bivariatesupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, according to Rusdi's research (2018) which shows that there is an effect of giving red guava juice on hemoglobin levels of anemic adolescent girls with p value = <0.001. This is in line with Handayani's (2021) study which showed that guava juice had an effect on increasing hemoglobin levels in adolescent girls.…”
Section: Bivariatesupporting
confidence: 92%
“…Iron expenditure must also be balanced with nutritional intake. Anemia in adolescents is related to the lack of intake of foods containing iron (Handayani, 2021).…”
Section: Univariate Analysismentioning
confidence: 99%
“…Another study conducted in adolescent females given red guava juice found a 0.6 g/dl increase in hemoglobin levels with p<0.05. 14 Based on the above explanation, this study aimed to analyze the effectiveness of giving crystal guava juice (Psidium guajava L. "Crystal") on hemoglobin levels in female adolescents with anemia.…”
Section: Introductionmentioning
confidence: 99%